Dampak Game Online Terhadap Remaja - Weni Gurita Aedi; Lisda Fitriana Masitoh; Yan Mitha Djaksana (CV. Multi Kreasi Media, 2023)
Current technological sophistication results in almost all activities related to the internet, including entertainment. Online games are part of the internet that are frequently visited and are very popular and can cause addiction that has a very high intensity. Because online games are one of the entertainment that teenagers really like to reduce fatigue and stress. If this activity is excessive it will result in addiction which has a negative impact on the lives of adolescents. Initially, online games served as entertainment to fill free time and reduce fatigue and stress. However, its function shifts into addiction if it is used excessively. The rise of online games has a negative effect if we are not wise in using these online game applications. Environmental conditions, in this case friends, are very influential on adolescents, this is because there are many games among adolescents, causing concern among parents about their children's learning achievements. Parents are worried that the more children are given access to use gadgets, the more likely children are to misuse gadgets to play online games. This service aims to find out and take the right steps to reduce online game addiction. Considering that online games are one of the entertainments that are much loved by all groups, especially teenagers, which can cause addiction. With the socialization of the negative impacts of online games carried out by the team of service lecturers, it is hoped that students will be able to control themselves when playing online games.